Duplications and losses in gene families of rust pathogens highlight putative effectors - Pendleton, Amanda L.; Smith, Katherine E.; Feau, Nicolas; Martin, Francis M.; Grigoriev, Igor V.; Hamelin, Richard; Nelson, C. Dana; Burleigh, J. Gordon; Davis, John M. (Frontiers in Plant Science, 2014)
Rust fungi are a group of fungal pathogens that cause some of the world’s most destructive diseases of trees and crops. A shared characteristic among rust fungi is obligate biotrophy, the inability to complete a lifecycle without a host. This dependence on a host species likely affects patterns of gene expansion, contraction, and innovation within rust pathogen genomes. The establishment of disease by biotrophic pathogens is reliant upon effector proteins that are encoded in the fungal genome and secreted from the pathogen into the host’s cell apoplast or within the cells. This study uses a comparative genomic approach to elucidate putative effectors and determine their evolutionary histories. We used OrthoMCL to identify nearly 20,000 gene families in proteomes of sixteen diverse fungal species, which include fifteen basidiomycetes and one ascomycete. We inferred patterns of duplication and loss for each gene family and identified families with distinctive patterns of expansion/contraction associated with the evolution of rust fungal genomes. To recognize potential contributors for the unique features of rust pathogens, we identified families harboring secreted proteins that: i) arose or expanded in rust pathogens relative to other fungi, or ii) contracted or were lost in rust fungal genomes. While the origin of rust fungi appears to be associated with considerable gene loss, there are many gene duplications associated with each sampled rust fungal genome. We also highlight two putative effector gene families that have expanded in Cqf that we hypothesize have roles in pathogenicity.